Analisis Kesesuaian Akad Musyarakah Mutanaqishah Pada Pembiayaan Griya iB Hasanah Dengan Fatwa Dsn No.73/Dsn-Mui/Xi/2008 di Bank BNI Syariah Kantor Cabang Bekasi - Astuti, Leni; Pahlevi, Rizal (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2018)
House prices that keep continue increasing have made people are rare to be able to buy houses incash. A way out for people who earn a minimum salary to get their own house is pay arrange or rent.This thesis describes the contract Musyarakah Mutanqishah in BNI Syariah Bank in financing Griya iBHasanah which is adjusted to the fatwa DSN No.73/DSN-MUI/XI/2008 (Musyarakah Mutanaqishah).The method that used in this research process is a qualitative descriptive analysis method. Datacollection is primary data, and secondary data. Primary data is obtained by interviewing the officialof BNI Syariah Bank. Library literature study was obtained from books, journals and documents thatrelated to the contract Musyarakah Mutanqishah. Data analysis technique done with three steps,namely data reduction, data presentation, and drawing conclusions from the results of the analysisof the data is proven by the accuracy of the data through triangulation techniques with sources. Theresults of this study indicate that the implementation of the contract Musyarakah Mutanaqishah infinancing Griya iB Hasanah in BNI Syariah Bank, Branch Office of Bekasi is in accordance with thefatwa dsn mui no.37/dsn-mui/ix/2008. But in its application there are discrepancies in aspects : first,musyarakah mutaqishah can be ‘ijarah’ to syarik or other side. Second, bear a loss appropriate withamount of capital. Third, the profits obtained from the ‘ujrah’ that are divided according to the agreedratio in the contract. while losses must be based on the proportion of ownership.